Estudio sobre cambios fisico-químicos durante la fermentación del pasto elefante en microsilos de laboratorio con tres niveles de melaza - Vargas Cordero, Ruth (1981)
Physical and chemical changes during the fermentation of elephant grass with three levels of sugar cane molasses, in laboratory silos. The effect of the adition of sugar cane molasses on the chemical composition and nutritive value of elephant grass (Pennisetum purpureum) silage, was studied utilizing laboratory silos. These silos were made from strong plastic bags holding about 50 kg of chopped fresh forage, combined with three levels of molasses (0 5 and 10% wet basis). A randomized blocks design with 3 replications was used. Differences among treatment means were determined by the Duncan's test. The laboratory analisis were: pH, volatile fatty acid and lactic acic content, soluble carbohidrates content, dry matter content, crude protein content and cell wall constituents content (NDF). As the level of molasses increased pH decreased and fatty, acetic, and lactic acids, tend to increase. Butiric acid content decreases with the adition of molasses. The positive effect of molasses was to increase soluble carbohidrates available to the bacteria allowing increases in dry matter content and crude protein content and decreases in the cell wall constituents. The use of the small laboratory silos was a practical and effective way to study the qualitative and quantitative effect of the addition of sugar cane molasses to the elephant grass during silage production.